2022
DOI: 10.1002/chem.202200370
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular (4+3) Cycloadditions of Oxidopyridinium Ions: Towards Daphnicyclidin A

Abstract: N-alkylation of 5-hydroxynicotinic acid esters with electrophiles containing diene functionality produces salts that undergo intramolecular (4 + 3) cycloaddition reactions upon heating in the presence of base. Initial studies used a three-carbon tether to join the pyridinium ion and diene, revealing some aspects of the inherent selectivity of the reaction with such substrates. Much more challenging was the synthesis of related species possessing only a two-carbon tether. Nevertheless, the cycloaddition of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As a final example, Harmata and co-workers recently developed the synthesis of the ABC ring system of daphnicyclidin A using an intramolecular [4 + 3] cycloaddition reaction of an oxidopyridinium ion ( Scheme 230 ). 302 Initially, the authors studied substrates with a three-carbon tether attached to the pyridinium ion. Thus, heating pyridinium substrates 476 , with dienes substituted at the C2-position, in the presence of Et 3 N as a base, triggered an intramolecular (4 + 3) cycloaddition to render a mixture of endo 477 and exo 477′ tricycles in good yields.…”
Section: Applications To Natural Product Synthesismentioning
confidence: 99%
“…As a final example, Harmata and co-workers recently developed the synthesis of the ABC ring system of daphnicyclidin A using an intramolecular [4 + 3] cycloaddition reaction of an oxidopyridinium ion ( Scheme 230 ). 302 Initially, the authors studied substrates with a three-carbon tether attached to the pyridinium ion. Thus, heating pyridinium substrates 476 , with dienes substituted at the C2-position, in the presence of Et 3 N as a base, triggered an intramolecular (4 + 3) cycloaddition to render a mixture of endo 477 and exo 477′ tricycles in good yields.…”
Section: Applications To Natural Product Synthesismentioning
confidence: 99%
“…In 2022, Harmata et al reported the comparatively short synthesis of the ABC-tricyclic building block 145 for daphnicyclidin A (Scheme 14). [29] An intramolecular (4 + 3) cycloaddition of the 3-hydroxypyridinium cation 144 at high temperature on a preparative scale enabled a rapid build-up of the required molecular complexity. The convergent synthesis of the hydroxypyridinium cation 144 was accomplished by N-alkylation of ethyl 5-hydroxynicotinate 143 with the tosylate 142.…”
Section: Synthetic Effortsmentioning
confidence: 99%
“… 5 Also noteworthy are the total syntheses of several Daphniphyllum alkaloids recently reported by Li. 9 Moreover, only a few studies have reported synthetic strategies toward compounds embodying tricyclic scaffolds (ABC rings) 6 as potential advanced precursors of the target alkaloids.…”
Section: Introductionmentioning
confidence: 99%